Pediatric Obesity: Pharmacokinetic Alterations and Effects on Antimicrobial Dosing. Issue 3 (27th February 2017) - Natale, Stephanie; Bradley, John; Nguyen, William Huy; Tran, Tri; Ny, Pamela; La, Kirsten; Vivian, Eva; Le, Jennifer
Abstract : Limited data exist for appropriate drug dosing in obese children. This comprehensive review summarizes pharmacokinetic (PK) alterations that occur with age and obesity, and these effects on antimicrobial dosing. A thorough comparison of different measures of body weight and specific antimicrobial agents including cefazolin, cefepime, ceftazidime, daptomycin, doripenem, gentamicin, linezolid, meropenem, piperacillin‐tazobactam, tobramycin, vancomycin, and voriconazole is presented. PubMed (1966–July 2015) and Cochrane Library searches were performed using these key terms: children, pharmacokinetic, obesity, overweight, body mass index, ideal body weight, lean body weight, body composition, and specific antimicrobial drugs. PK studies in obese children and, if necessary, data from adult studies were summarized. Knowledge of PK alterations stemming from physiologic changes that occur with age from the neonate to adolescent, as well as those that result from increased body fat, become an essential first step toward optimizing drug dosing in obese children. Excessive amounts of adipose tissue contribute significantly to body size, total body water content, and organ size and function that may modify drug distribution and clearance. PK studies that evaluated antimicrobial dosing primarily used total (or actual) body weight (TBW) for loading doses and TBW or adjusted body weight for maintenance doses, depending on the drugs' properties and dosing units. PK studies in obese children are imperative to elucidate drug distribution, clearance, and, consequently, the dose required for effective therapy in these children. Future studies should evaluate the effects of both age and obesity on drug dosing because the incidence of obesity is increasing in pediatric patients.